Rethinking avoidance of English phrasal verbs by Arab learners - Abu Jamil, Basem Saleh, author; Flahive, Douglas, advisor; Berry, Nancy, committee member; Grim, Frederique, committee member (Colorado State University. Libraries, 2010)
There is a long-standing controversy about the causes of underproduction (avoidance) of structures in second language learning/acquisition. A significant field of research has focused on one lexicalized phrase, the English phrasal verb. The present study explores the cultural dimensions of the avoidance of English phrasal verbs among 160 Arab learners of English. It examines the impact of educational background (EFL, ESL), levels of proficiency (advanced, intermediate), and the inherent semantic complexity of phrasal verb (literal, semi-transparent, figurative) on the avoidance of phrasal verbs. It also explores the role the environmental background plays in comprehending phrasal verbs. Although Arab learners in the study tended to under-use English phrasal verbs, there were significant developmental differences ranging from avoidance to nonavoidance based on participants’ educational background and level of proficiency and the semantic properties of phrasal verbs. This study calls into question straightforward interpretation of the avoidance phenomenon. Although these findings support previous studies’ results, they do not support previous studies that show that L1-L2 differences might motivate learners to develop a genuine avoidance; Arab learners in this study did not avoid literal phrasal verbs. The study offers interesting clues to the success of advanced ESL students in learning and mastering phrasal verbs.
Covers not scanned.
Keywords: English language -- Verb phrase; English language -- Study and teaching (Higher) -- Arab speakers; English language -- Study and teaching (Higher) -- Foreign speakers